Workshop pembuatan media pembelajaran interaktif dalam memenuhi tuntutan pembelajaran Abad 21 - Lalu Muhammad Fauzi; Muhammad Gazali; Husnul Mukti; Baiq Fitri Rahmawati (Universitas Hamzanwadi, 2021)
Teachers have a crucial role in fostering and directing students to compete in all fields. The era of globalization requires teachers to improve their pedagogical competence, especially in professional competence. Teachers are needed to be proficient in understanding the subject matter, but teachers must also be able to use and utilize technology as a medium and source of learning. It is vital to provide workshops or training to create and use interactive learning media for smooth learning during the current COVID-19 pandemic. The workshop was held for three days with details on the provision of material on the first day, the practice of making media on the second day, and evaluation of the products produced by the participants on the third day, which was held from Saturday, August 5, to Monday, August 7, 2021, at SDN 3 Sembalun Bumbung. The workshop results illustrate that participants have been able to create interactive learning media using the AutoPlay Media Studio 8.0 application